Characterization a Novel Butyric Acid-Producing Bacterium Collinsella aerofaciens Subsp. Shenzhenensis Subsp. Nov - Qin, Panpan; Zou, Yuanqiang; Dai, Ying; Luo, Guangwen; Zhang, Xiaowei; Xiao, Liang (Microorganisms (Basel), 2019)
Butyrate-producing bacteria can biosynthesize butyrate and alleviate inflammatory diseases. However, few studies have reported that the genus Collinsella has the ability to produce butyric acid. Here, our study depicts a Collinsella strain, which is a rod-shaped obligate anaerobe that is able to produce butyric acid. This microorganism was isolated from a human gut, and the optimal growth conditions were found to be 37 °C on PYG medium with pH 6.5. The 16S rRNA gene sequence demonstrated that this microorganism shared 99.93% similarity with C. aerofaciens ATCC 25986T, which was higher than the threshold (98.65%) for differentiating two species. Digital DNA–DNA hybridization and average nucleotide identity values also supported that this microorganism belonged to the species C. aerofaciens. Distinct phenotypic characteristics between TF06-26 and the type strain of C. aerofaciens, such as the fermentation of D-lactose, D-fructose and D-maltose, positive growth under pH 5 and 0.2% (w/v) cholate, suggested this strain was a novel subspecies. Comparative genome analysis revealed that butyric acid kinase and phosphate butyryltransferase enzymes were coded exclusively by this strain, indicating a specific butyric acid-producing function of this C. aerofaciens subspecies within the genus Collinsella. Thus, Collinsella aerofaciens subsp. shenzhenensis subsp. nov. was proposed, with set strain TF06-26T (=CGMCC 1.5216T = DSM 105138T) as the type strain.